Illicit drug use in sexual settings ('chemsex') and HIV/STI transmission risk behaviour among gay men in South London: findings from a qualitative study. (9th July 2015) - Bourne, A; Reid, D; Hickson, F; Torres-Rueda, S; Weatherburn, P
Abstract : Background: 'Chemsex' is a colloquial term used in the UK that describes sex under the influence of psychoactive substances (typically crystal methamphetamine, mephedrone and gamma-hydroxybutyric acid (GHB)/gamma-butyrolactone (GBL)). Recently, concern has been raised as to the impact of such behaviour on HIV/sexually transmitted infection (STI) transmission risk behaviour, which this qualitative study aimed to explore via semistructured interviews with gay men living in three South London boroughs. Methods: Interviews were conducted with 30 community-recruited gay men (age range 21–53) who lived in the boroughs of Lambeth, Southwark and Lewisham, and who had used crystal methamphetamine, mephedrone or GHB/GBL either immediately before or during sex with another man during the previous 12 months. Data were subjected to a thematic analysis. Results: Chemsex typically featured more partners and a longer duration than other forms of sex, and the relationship between drug use and HIV/STI transmission risk behaviour was varied. While some men believed that engaging in chemsex had unwittingly led them to take risks, others maintained strict personal rules about having safer sex. Among many participants with diagnosed HIV, there was little evidence that the use of drugs had significantly influenced their engagement in condomless anal intercourse (primarily with other men believed to be HIV positive), but their use had facilitated sex with more men and for longer. Conclusions: Analysis revealed that, within this sample, chemsex is never less risky than sex without drugs, and is sometimes more so. Targeted clinic-based and community-based harm reduction and sexual health interventions are required to address the prevention needs of gay men combining psychoactive substances with sex.